Proposed Diagnostic Criteria for the Case Definition of Amniotic Fluid Embolism in Research Studies. Issue 3 (September 2017) - Clark, S.L.; Romero, R.; Dildy, G.A.; Callaghan, W.M.; Smiley, R.M.; Bracey, A.W.; Hankins, G.D.; D'Alton, M.E.; Foley, M.; Pacheco, L.D.; Vadhera, R.B.; Herlihy, J.P.; et al.
Abstract : ( Am J Obstet Gynecol. 2016;215(4):408–412) A lack of diagnostic criteria for amniotic fluid embolism (AFE) has hindered the understanding and management of this uncommon but often fatal condition. Some previous reports have defined AFE by criteria not specific to AFE, and included only patients who died, possibly excluding women less severely affected by AFE. Other reports have used widely varying criteria and likely included patients suffering from conditions other than AFE. The possibly skewed results of these studies and the lack of a definition of AFE are troubling as AFE is one of the leading causes of maternal death in developed countries.